INCIDENCE OF CORONARY ARTERY ANOMALY IN SULAIMANI CARDIAC HOSPITAL - Mohialdeen, Dara M.; Abdalla, Razhan Y.; Hassan, Kawa (Journal of Sulaimani Medical College, 2022)
Background Coronary arteries are classified traditionally into three different groups according to their anatomy, normal anatomy, anatomical variations, and anomaly. The incidence of coronary artery anomaly (CAA) can vary from as low as 0.2% to as high as 5.64% of the general population. Objectives To find the incidence of coronary artery anomalies in the Sulaimani Cardiac Center. Materials and Methods A Prospective case study was carried out on patients undergoing emergency and elective coronary catheterization in Sulaimani cardiac hospital from January 2021 to January 2022. After a complete history and physical examination, their coronary angiogram reports were evaluated for the coronary anomaly. Results A total of 3,127 patients were evaluated, with coronary anomalies in 144 patients with an incidence of 4.6%. The mean age was 60.2± 11, ranging from 24 to 92 years. The male gender was 66.7%(n=96). The presenting complaint in this study was predominantly chest pain, 78.5%(n=48). The acute coronary syndrome was the cause of urgent coronary angiography in 22.9% (n=33). The myocardial bridge was the most predominant among our patients 41% (n=59), followed by the Separate origins of the Left Anterior Descending Artery and Left Circumflex Artery in the Left sinus of the Valsalva, 38.2%(n=55). While Anomalies of coronary termination (fistula) were found in 4.9% (n=7), Conclusion Coronary artery anomalies are uncommon findings in patients undergoing coronary angiography with an incidence of 4.6%, The most common anomaly detected in our study was myocardial bridging.
Keywords: Coronary artery anomaly; Myocardial bridge; Sudden death